Kelayakan Inovasi Teknologi Pakan Lengkap Terfermentasi Pada Usaha Ternak Sapi Potong - Agus Hermawan; Heri Kurnianto; Forita D. Arianti; Indrie Ambarsari (Universitas Muhammadiyah Purworejo, 2019)
In the beef cattle business, feed is the second largest cost component after feeder purchases. To increase the efficiency of feed use and business efficiency, the complete fermented feed was introduced at the beef cattle production center in Sumberejo Village, Ngablak District, Magelang Regency. The complete feed consists of forage, rice bran, minerals, molasses, and salt, fermented with local microorganisms (MOL) made from the beef rumen. Feed was given to 5 beef cattle breeders and compared with the breeders' feed. The financial feasibility of the two feeding modes was compared. The results of the analysis show that complete fermented feed can increase daily body weight gain (PBBH) from 0.48 to 1.16 kg, shorten the fattening period from 13.5 months to 11 months, reduce the amount and cost of feed needed, reduce labor requirements. . , as well as increasing farmers' income. If all costs are taken into account, the fattening of livestock using the farmer's feed system which previously lost (R / C = 0.994) becomes profitable with complete fermented feed (R / C = 1.374).